The Influence of Didactic VR Programs on Educational Motivation, Mental States and Creativity in Students - Zikeeva E.A.; Selivanov V.V.; Kapustina V.U.; Strizhova I.V. (Психолого-педагогические исследования)
The use of modern didactic programs in mathematics in virtual reality (VR) requires approbation, proof of efficiency and environmental friendliness. VR properties: the ability to animate (perform actions with objects), interactivity and immersion in the information space are especially important for the training of future engineers, mathematicians and programmers. However, such programs today are still a poorly understood innovation, causing scientific controversy. The purpose of the presented study is to substantiate the effectiveness of didactic VR programs in teaching university students in technical areas, through determining the level of knowledge gained, the impact on the formation of educational motivation and the level of creativity among students in the study of higher mathematics. The methodological basis of the research was made up of the main provisions of the psychology of virtual reality, virtual ontology (V.A. Barabanshchikov, V.V. Selivanov). The assessment of changes in educational motivation was carried out using the methodology of A.A. Rean and V.A. Yakunin (modified by N.Ts. Badmaeva). Diagnostics of the level of creativity was carried out using the Johnson questionnaire, adapted by E.E. Tunic. As a result, it was shown that the students involved in the work with VR programs, at the level of reliable statistical significance, increase the indicators for the parameters of educational motivation, activity and creativity.